Early developmental intervention programmes provided post hospital discharge to prevent motor and cognitive impairment in preterm infants - Spittle, A.; Orton, J.; Anderson, P.; Boyd, Roslyn; Doyle, L. (John Wiley & Sons, Ltd., 2015)
Background: Infants born preterm are at increased risk of developing cognitive and motor impairment compared with infants born at term. Early developmental interventions have been provided in the clinical setting with the aim of improving overall functional outcomes for these infants. Long-term benefits of these programmes remain unclear. Objectives: Primary objective: To compare the effectiveness of early developmental intervention programmes provided post hospital discharge to prevent motor or cognitive impairment in preterm (< 37 weeks) infants versus standard medical follow-up of preterm infants at infancy (zero to < three years), preschool age (three to < five years), school age (five to < 18 years) and adulthood (≥ 18 years). Secondary objectives: To perform subgroup analyses to determine the following • Effects of gestational age, birth weight and brain injury (periventricular leukomalacia (PVL)/intraventricular haemorrhage (IVH)) on cognitive and motor outcomes when early intervention is compared with standard follow-up ∘ Gestational age: < 28 weeks, 28 to < 32 weeks, 32 to < 37 weeks.∘ Birth weight: < 1000 grams, 1000 to < 1500 grams, 1500 to < 2500 grams ∘ Brain injury: absence or presence of grade III or grade IV IVH or cystic PVL (or both) or an abnormal ultrasound/magnetic resonance image (MRI) before initiation of the intervention. • Effects of interventions started during inpatient stay with a post-discharge component versus standard follow-up care. • Effects of interventions focused on the parent-infant relationship, infant development or both compared with standard follow-up care. To perform sensitivity analysis to identify the following. • Effects on motor and cognitive impairment when early developmental interventions are provided within high-quality randomised trials with low risk of bias for sequence generation, allocation concealment, blinding of outcome measures and selective reporting bias.Search methods: The search strategy of the Cochrane Neonatal Review Group was used to identify randomised and quasi-randomised controlled trials of early developmental interventions provided post hospital discharge. Two review authors independently searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE Advanced, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO and EMBASE (1966 to August 2015). Selection criteria: Studies included had to be randomised or quasi-randomised controlled trials of early developmental intervention programmes that began within the first 12 months of life for infants born before 37 weeks' gestational age. Interventions could commence on an inpatient basis but had to include a post-discharge component for inclusion in this review. Outcome measures were not prespecified, other than that they had to assess cognitive outcomes, motor outcomes or both. Rates of cerebral palsy were documented. Data collection and analysis: Two independent review authors extracted and entered data. Cognitive and motor outcomes were pooled by four age groups: infancy (zero to < three years), preschool age (three to < five years), school age (five to < 18 years) and adulthood (≥ 18 years). Meta-analysis using RevMan 5.1 was carried out to determine the effects of early developmental interventions at each age range. Subgroup analyses focused on gestational age, birth weight, brain injury, commencement of the intervention, focus of the intervention and study quality. Main results: Twenty-five studies met the inclusion criteria (3615 randomly assigned participants). Only 12 of these studies were randomised controlled trials with appropriate allocation concealment. Variability was evident with regard to focus and intensity of the intervention, participant characteristics and length of follow-up. Meta-analysis led to the conclusion that intervention improved cognitive outcomes at infancy (developmental quotient (DQ): standardised mean difference (SMD) 0.32 standard deviations (SDs), 95% confidence interval (CI) 0.16 to 0.47; P value < 0.001; 16 studies; 2372 participants) and at preschool age (intelligence quotient (IQ); SMD 0.43 SDs, 95% CI 0.32 to 0.54; P value < 0.001; eight studies; 1436 participants). However, this effect was not sustained at school age (IQ: SMD 0.18 SDs, 95% CI -0.08 to 0.43; P value = 0.17; five studies; 1372 participants). Heterogeneity between studies for cognitive outcomes at infancy and at school age was significant. With regards to motor outcomes, meta-analysis of 12 studies showed a significant effect in favour of early developmental interventions at infancy only; however, this effect was small (motor scale DQ: SMD 0.10 SDs, 95% CI 0.01 to 0.19; P value = 0.03; 12 studies; 1895 participants). No effect was noted on the rate of cerebral palsy among survivors (risk ratio (RR) 0.82, 95% CI 0.52 to 1.27; seven studies; 985 participants). Little evidence showed a positive effect on motor outcomes in the long term, but only five included studies reported outcomes at preschool age (n = 3) or at school age (n = 2). Authors' conclusions: Early intervention programmes for preterm infants have a positive influence on cognitive and motor outcomes during infancy, with cognitive benefits persisting into preschool age. A great deal of heterogeneity between studies was due to the variety of early developmental intervention programmes tested and to gestational ages of included preterm infants; thus, comparisons of intervention programmes were limited. Further research is needed to determine which early developmental interventions are most effective in improving cognitive and motor outcomes, and to discern the longer-term effects of these programmes.